Injector tests - Newland, Ross N. (My University, 1906)
The injector is an instrument by means of which a jet of steam acting on a jet of water with which it mingles and by which it is condensed can impart to the resulting jet of water a velocity sufficient to overcome a pressure equal to or greater than the initial pressure of the steam. The ability of the injector to force water against a pressure equal to that of the working steam makes it a very valuable instrument for supplying a boiler with feed-water. The essential difference between the injector and the other forms of jet pumps is, that a great part of its energy is derived from the condensation of the steam by the water. The jet pump works on the principle that when a small volume of a fluid moving at a high velocity mingles with a larger volume, it can move the whole volume at a low velocity. This principle enters into the working of the injector for a small amount of steam issuing from a boiler at a high velocity will impart to a large volume of water a considerable velocity, but this is only a small part of the energy developed in the injector. The greater part of the energy, as has already been stated, comes from the heat contained in the steam. On the condensation of the steam this heat is given up and is converted into mechanical energy. For the invention of the injector we are indebted to Henry Gifford an eminent French engineer. Gifford was interested in the development of aeronautic apparatus and it became necessary for him to have some light and simple instrument to feed a small boiler which was to be carried by a balloon. The only boiler feeder then obtainable was a heavy and cumbersome steam pump so he directed his energies toward the invention of some other kind of apparatus. He was acquainted with the methods of pumping water with the steam jet and after a thorough study of the dynamics of steam he concluded that there was sufficient latent energy in steam, not only to move a large volume of water but to force it into the boiler from which the steam came.
Citation: Newland, Ross N. Injector tests. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Mechanical Engineering; Injectors; Boilers; Theses